Тенденції та закономірності формування і використання інвестиційних ресурсів регіону - Моцок, А.В. (Культура народов Причерноморья, 2004)
В статье исследуются тенденции и закономерности формирования и использования инвестиционных ресурсов региона, анализируются основные их источники, а именно сбережения населения, прибыль предприятий, банковский капитал, реимпортированный капитал, иностранные инвестиции. Определены необходимые меры для повышения эффективности формирования и использования инвестиционных ресурсов региона. In the article investigate the tendencies and regularities of the forming und using the regions' investment recourses, analyzing the basic investment source, in particular it's the personal savings of population, the profits of enterprise, the banking capital, the capital which reimport and foreign investment. In research specified the necessary arrangements to increase the efficiency of forming und using regions' investment recourse.